2013
DOI: 10.1016/j.bone.2012.09.025
|View full text |Cite
|
Sign up to set email alerts
|

High osteoporotic fracture risk and CVD risk co-exist in postmenopausal women

Abstract: 32 Results: Women with higher 10 year risk of major osteoporotic had significantly higher cardiovascular risk 33 (4.634% vs 8.36%, p =0.001). In multiple regression analysis, 5-year CVD risk was significantly associated with 34 the 10-year risk of having major osteoporotic (β=0.095, p=0.001) and hip (β =0.055, p=0.001) fracture.35 Women with the highest CVD risk were 5.4 times more likely to have higher risk of major osteoporotic fracture. 36 Conclusions: Fracture risk, determined by using a multiple risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
1
5
0
1
Order By: Relevance
“…What is more, the 10-year risk of fatal CVD risk, observed in that group of patients, significantly correlated with the 10-year risk of major fractures and hip fractures. We also found similar results in the literature: women with the highest risk of CVD have a higher risk of major osteoporotic fractures [10], which may be associated with the pathophysiological disorders common in both processes. A common pathogenesis of the two medical conditions may, for example, indicate mutual correlations of medicinal agents, exerted on particular disease entities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…What is more, the 10-year risk of fatal CVD risk, observed in that group of patients, significantly correlated with the 10-year risk of major fractures and hip fractures. We also found similar results in the literature: women with the highest risk of CVD have a higher risk of major osteoporotic fractures [10], which may be associated with the pathophysiological disorders common in both processes. A common pathogenesis of the two medical conditions may, for example, indicate mutual correlations of medicinal agents, exerted on particular disease entities.…”
Section: Discussionsupporting
confidence: 91%
“…It is an important fact that both osteoporosis and cardiovascular disorders are associated with a significant risk of disability and mortality, while only a few studies have attempted to analyse both diseases as related conditions [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…28 Makovey et al reported that risk of osteoporotic fracture was significantly correlated with Framingham risk score. 17 In the present study, vascular function assessed on FMD and NID and vascular structure assessed using brachial artery IMT were impaired as FRAX risk of osteoporotic fracture increased. This suggests that risk of osteoporotic fracture is associated with vascular function and vascular structure.…”
Section: Discussionmentioning
confidence: 42%
“…6, 10 Clinical and epidemiological studies have shown a link between osteoporosis and cardiovascular disease. [15][16][17] Although osteoporosis and cardiovascular disease share many common risk factors, growing evidence also indicates that there are common pathophysiological mechanisms underlying these diseases. 18 Both vascular calcification and bone mineralization are regulated by several shared boneassociated proteins, such as osteocalcin, osteopontin, bone morphogenetic proteins (BMP), and osteoprotegerin.…”
Section: Risk Of Osteoporotic Fracture and Atherosclerosismentioning
confidence: 99%
“…Полученные результаты были сходны с единичными исследованиями в этой области. Работа по изучению взаимосвязи ССР и риска ОПП была проведена австралийскими учеными с применением Фремингемской шкалы для оценки риска ССЗ и австралийской модели FRAX ® без включения МПК для оценки риска ОПП у 358 женщин в возрасте 45-74 лет [26]. Авторы продемонстрировали, что женщины с высоким 10-летним риском основных ОПП имели более высокий ССР 4,63% vs 8,36%, (р=0,001).…”
Section: Discussionunclassified